Skills mismatch a study on the demand and supply of TVET in Region XII (SOCCSKSARGEN) - Arreza, Katrina Y.
One possible reason for the unemployment problem was said to be skills mismatch. In Region XU (SOCCSKSARGEN) unemployment rate for April 2002 was 13.5%. The study aimed to find out if there was skills mismatch in the region and also to know the reasons behind it. Specifically, the study focused on the TVET sector because most of the labor force in every locality belonged to the semi-skilled and skilled workers. Background analysis on the industry and labor force profile of the region were made to have an overview of the potential ends users and possible clients or students of TVET. Primary method of analysis was qualitative analysis, in particular the descriptive method, because of the unavailability of time series data. Publications like the National Statistical Coordination Board Yearbook and the GEM Indicators were the main source of data for the background analysis. Moreover, the correlation method was used, in terms of the derived demand (enrollment) and supply (graduates), in order to support the descriptive analysis. Survey of key informants-TVET providers, TVET students, and government institutions-was also attained for further support on the analysis. The results showed that the region produces graduates mostly with maritime, health, and information technology degrees. In contrast, the industry needed workers in food processing and construction. Not only that, TVET graduates have to compete with graduates having bachelors degree. Therefore, it was concluded that there is skills mismatch in the region. One viable reason was that the private TVET providers were offering courses that they believed attract students, not what the industry needed. They are more focused on monetary benefits. It was recommended that further study be done on the topic because the TVET sector has a culture that can be a worthy factor for economic development.